A biofilm model to understand the onset of sulfate reduction in denitrifying membrane biofilm reactors. Issue 3 (1st November 2012) - Tang, Youneng; Ontiveros‐Valencia, Aura; Feng, Liang; Zhou, Chen; Krajmalnik‐Brown, Rosa; Rittmann, Bruce E.
Abstract This work presents a multispecies biofilm model that describes the co‐existence of nitrate‐ and sulfate‐reducing bacteria in the H2‐based membrane biofilm reactor (MBfR). The new model adapts the framework of a biofilm model for simultaneous nitrate and perchlorate removal by considering the unique metabolic and physiological characteristics of autotrophic sulfate‐reducing bacteria that use H2 as their electron donor. To evaluate the model, the simulated effluent H2, UAP (substrate‐utilization‐associated products), and BAP (biomass‐associated products) concentrations are compared to experimental results, and the simulated biomass distributions are compared to real‐time quantitative polymerase chain reaction (qPCR) data in the experiments for parameter optimization. Model outputs and experimental results match for all major trends and explain when sulfate reduction does or does not occur in parallel with denitrification. The onset of sulfate reduction occurs only when the nitrate concentration at the fiber's outer surface is low enough so that the growth rate of the denitrifying bacteria is equal to that of the sulfate‐reducing bacteria. An example shows how to use the model to design an MBfR that achieves satisfactory nitrate reduction, but suppresses sulfate reduction. Biotechnol. Bioeng. 2013; 110: 763–772. © 2012 Wiley Periodicals, Inc.